2000
DOI: 10.1038/modpathol.3880126
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Grading of Breast Cancer: Linkage of Patient Outcome with Level of Pathologist Agreement

Abstract: In the histologic grading of invasive breast cancer with the Nottingham modification of the ScarffBloom-Richardson grading scheme (NSBR), it has been found that when pathologists disagree, they tend not to disagree by much. However, if tumor grade is to be used as an important parameter in making treatment decisions, then even this generally small degree of pathologist variability in assessing grade needs to be correlated with patient outcome.Findings from the Nottingham/Tenovus Primary Breast Cancer Study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 12 publications
0
77
0
2
Order By: Relevance
“…Together, these unique signatures may underlie the molecular basis of the current pathological grading systems for breast cancer. Such systems rely mainly on histomorphological criteria, which, although highly successful in discriminating grade I from grade III tumors, are inadequate to score grade II tumors consistently (4). This difficulty may be explained by the overlapping nature of grade II signature with those of grade I and grade III.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, these unique signatures may underlie the molecular basis of the current pathological grading systems for breast cancer. Such systems rely mainly on histomorphological criteria, which, although highly successful in discriminating grade I from grade III tumors, are inadequate to score grade II tumors consistently (4). This difficulty may be explained by the overlapping nature of grade II signature with those of grade I and grade III.…”
Section: Discussionmentioning
confidence: 99%
“…DCIS was classified according to the European classification scheme (5): low-grade DCIS is characterized by a clinging, cribriform, or micropapillary proliferation of small, monomorphic cells with rare mitoses, whereas high-grade DCIS is characterized by a solid or clinging proliferation of large, pleomorphic cells with frequent mitoses. IDC was classified according to by the Nottingham combined histological grade (4). Estrogen receptor (ER) and progesterone receptor (PR) expression were determined by immunohistochemical staining (negative when none of the tumor cell nuclei showed staining), and Her-2 expression determined by immunohistochemistry or fluorescence in situ hybridization (FISH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grading of malignancy of ductal carcinomas was evaluated according to the Scarff, Bloom and Richardson criteria as suggested by Nottingham City Hospital Pathologists (Dalton et al, 2000). Tumour staging was performed according to parameters of the TNM system (Singletary and Connolly, 2006).…”
Section: Tissue Samplesmentioning
confidence: 99%
“…These sections are typically rich in content since various cell types, cellular organization, cell state and health, and cellular secretion can be characterized by a trained pathologist in spite of inter-and intraobserver variations [3]. A recent review for the analysis and application of H&E sections can be found in [4,5]; however, from our perspective, three key concepts have been introduced to establish the trend and direction of the research community.…”
Section: Review Of Previous Researchmentioning
confidence: 99%